109k views
2 votes
Use Theorem to find ℒ{f(t)}.
f(t) = (et − e−t)2

User Zenixo
by
5.3k points

1 Answer

2 votes

Answer:


(3s^2-4)/(s(s^2-4))

Explanation:

Here, the question is to find the Laplace transformation of
f(t)

where,
f(t)=(e^t-e^(-t))^2

We know that for
t>0,
\mathcal{L}\{f(t)\} =\int_0^(\infty) e^(-st)f(t)dt


\mathcal{L}\{e^(at)\}=\int_0^(\infty) e^(-st)e^(at)dt


\Rightarrow \mathcal{L}\{e^(at)\}=\int_0^(\infty) e^((a-s)t)dt


\Rightarrow \mathcal{L}\{e^(at)\}=\left[\frac { e^((a-s))}{a-s}\right]_0^(\infty)


\Rightarrow \mathcal{L}\{e^(at)\}=\frac { 1}{s-a}\cdots(i)

Here, we have
f(t)=(e^t-e^(-t))^2


\Rightarrow f(t)=(e^t)^2+(e^(-t))^2-2(e^t)(e^(-t))


\Rightarrow f(t)=e^(2t)+e^(-2t)-2e^(0t)

So, the laplace transformation of
f(t) is


\mathcal{L}\{f(t)\}=\mathcal{L}\{e^(2t)+e^(-2t)-2e^(0t)\}


\Rightarrow \mathcal{L}\{f(t)\}=\mathcal{L}\{e^(2t)\}+\mathcal{L}\{e^(-2t)\}+\mathcal{L}\{e^(0)\}

Now, using equation
(i)


\mathcal{L}\{f(t)\}=(1)/(s-2)+(1)/(s-(-2))+(1)/(s-0)


\Rightarrow \mathcal{L}\{f(t)\}=(1)/(s-2)+(1)/(s+2)+(1)/(s)


\Rightarrow \mathcal{L}\{f(t)\}=(3s^2-4)/(s(s^2-4))

Hence, the Lapelace transformation of
f(t)=(e^t-e^(-t))^2 is


(3s^2-4)/(s(s^2-4)).

User Kirin Yao
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.